Prebiotic mannan oligosaccharide diet improves health status of the digestive system of marron, Cherax tenuimanus (Smith, 1912) - Sang, Huynh; Fotedar, Ravi (Food Products Press and Haworth Press Inc., 2010)
The aim of this experiment was to determine the effects of dietary supplementation with mannan oligosaccharide (MOS; BioMos, Alltech, USA) on the gut microbiota and histology of marron, Cherax tenuimanus. Marron were fed six different diets supplemented with 0%, 0.05%, 0.1%, 0.2%, 0.4%, and 0.8% of MOS for a duration of 112 days. Total bacteria in the gut were highest when marron were fed diets which included 0.1% to 0.4% BioMos, whereas total bacteria/Vibrio spp. ratio was highest in the marron fed 0.4% BioMos diet only. The marron fed 0.2% and 0.4% BioMos diets showed normal morphology and higher densities of microvilli, and thicker layer of gut epithelium than other inclusion rates. The results suggest that application of 0.2% to 0.4% of MOS in the diet improves digestive system health in marron.